Business practices among tour boat operators of Royal Belum-Temenggor, Gerik - Kamarudin, Khairul Hisyam (2014)
This paper analyses the business practices among tour boat in Royal Belum and Temenggor (RBT) Forest Park, Malaysia, regarding the development of business and entrepreneurship based on tourism activities in protected areas. Series of questionnaire-guided interview and focus group meeting were carried out for information gathering processes. Ten boat operators and representatives from union for local tour boat operators in RBT have participated in the survey. The study indicated the local tour boat association has played a crucial role in safeguarding the welfare of boat operators by protecting local tourism market from outsiders (especially the foreign and big capital investors/companies) while making sure healthy competition among members. The study indicates that majority of local tour boat operators have started their business as worker for other tour boat operators, before slowly climbing the business ladder after capable to saving money and then renting or purchasing small size/capacity speedboats for a small scale operation. After being operating for a sometime, these small operators were able to create substantial internal funds normally from their savings and personal loans to re-invent for business expansion. In the case of RBT, it is worth mention that the local operators are a group of resilience tourism entrepreneurs whereby majority of them are considered as self-made entrepreneurs (learning through experience) without or with a minimal assistance and support from government agencies. In terms of operation, most of the local operators are utilizing modern technology especially internet for enabling them keeping up with market demand and expectation of potential tourists. Online booking may has increase interest among tourists where they can settle everything in a more convenient way before want to RBT. However, in light of positive prospects of tourism, this sector is facing challenges in making sure their businesses are making money to stay afloat such as seasonal pattern and issue of relocation to a ‘new’ temporary jetty which reduced the number of tourists’ to RBT significantly. Respondents also highlighted the issue of lack of involvement in marketing/promotional of tourism in RBT at international platform. The paper concludes with brief outlook on the future prospect of rural tourism program in fostering local tour boat operating businesses and entrepreneurship culture in the rich mega biodiversity area of Royal Belum.